2014
DOI: 10.1177/0269215514542638
|View full text |Cite
|
Sign up to set email alerts
|

Participant and caregiver experience of the Nintendo Wii SportsTM after stroke: qualitative study of the trial of WiiTM in stroke (TWIST)

Abstract: The Wii™ may provide an engaging and flexible form of rehabilitation with relatively high reported usage rates in a home setting. The Wii™ was acceptable to this sample of patients and their caregivers in home-based rehabilitation of the arm following stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 21 publications
6
92
0
3
Order By: Relevance
“…The average RPE for the virtual therapist application as "somewhat hard" (QN7 with the virtual therapist application and the apple-catching game (when set up by the lead researcher) suggest that through personalisation of the range of movement, speed, and duration of activities, the PST system was able to maintain the level of challenge for those with a wide range of impairments following stroke. There was strong agreement between data sets that the apple-catching game was the easier task (QN6, QL11 Similar to other studies [36,40], the use of the hands-free system was essential for the majority of participants in the present study, several of whom had been unable to use the hand-held movement sensors when they had tried to use VR gaming technologies in the past (QL4 table 2). However, field notes showed that only two participants were able to attach the movement sensors themselves, thereby limiting feasibility of independent set-up (QL7 table 2).…”
Section: The Pst System Was Feasible To Usesupporting
confidence: 83%
See 1 more Smart Citation
“…The average RPE for the virtual therapist application as "somewhat hard" (QN7 with the virtual therapist application and the apple-catching game (when set up by the lead researcher) suggest that through personalisation of the range of movement, speed, and duration of activities, the PST system was able to maintain the level of challenge for those with a wide range of impairments following stroke. There was strong agreement between data sets that the apple-catching game was the easier task (QN6, QL11 Similar to other studies [36,40], the use of the hands-free system was essential for the majority of participants in the present study, several of whom had been unable to use the hand-held movement sensors when they had tried to use VR gaming technologies in the past (QL4 table 2). However, field notes showed that only two participants were able to attach the movement sensors themselves, thereby limiting feasibility of independent set-up (QL7 table 2).…”
Section: The Pst System Was Feasible To Usesupporting
confidence: 83%
“…Commercially available VR gaming technologies (such as the Nintendo Wii, Microsoft Kinect, Razer Hydra and Leap Motion) have become increasingly popular as motivating and relatively cheap alternatives [33,34]. However, issues of acceptability and feasibility have been noted, particularly in those with more severe disability due to the large range of movement, coordination and speed required to play the games, the degree of coordination and dexterity necessary to use movement sensors and the demoralising effect of "negative" feedback [35,36,37,38,39,40]. As a result, some teams have adapted low-cost, commercially available VR gaming devices for use in rehabilitation [39,40,41,42].…”
mentioning
confidence: 99%
“…Researchers have begun to pilot in-home, patient-led virtual reality gaming for upper limb rehabilitation in individuals with cerebral palsy 13,14 and stroke. [15][16][17][18][19][20] Clinically meaningful improvements in motor function were reported in 4 of 5 small-sample prospective studies. 15,[17][18][19] However, minimal gains in everyday use of the weaker arm (an outcome of importance to stakeholders) were realized.…”
mentioning
confidence: 99%
“…It however lacks assistive feedback which is present with most robotic devices [81]. Nevertheless, clinical trials with the system for patients undergoing stroke rehabilitation have reported that it is both enjoyable and beneficial [82], and both patients and caregivers have reported high use rates in a home setting [83]. The PlayStation EyeToy is a similar gaming console that uses a digital webcam to track interaction.…”
Section: Challenges To Adoption and Accessibility To Robot-assisted Rmentioning
confidence: 99%